Potential Therapeutic Applications of Pulmonary Surfactant Lipids in the Host Defence Against Respiratory Viral Infections - Ji, Jianjian; Sun, Ling; Luo, Zichen; Zhang, Ying; Xianzheng, Wang; Liao, Yingzhao; Tong, Xie; Shan, Jinjun (Frontiers in Immunology, 2021)
Pulmonary surfactant is a complex and highly surface-active material. It covers the alveolar epithelium and consists of 90% lipids and 10% proteins. Pulmonary surfactant lipids together with pulmonary surfactant proteins facilitate breathing by reducing surface tension of the air-water interface within the lungs, thereby preventing alveolar collapse and the mechanical work required to breathe. Moreover, pulmonary surfactant lipids, such as phosphatidylglycerol and phosphatidylinositol, and pulmonary surfactant proteins, such as surfactant protein A and D, participate in the pulmonary host defense and modify immune responses. Emerging data have shown that pulmonary surfactant lipids modulate the inflammatory response and antiviral effects in some respiratory viral infections, and pulmonary surfactant lipids have shown promise for therapeutic applications in some respiratory viral infections. Here, we briefly review the composition, antiviral properties, and potential therapeutic applications of pulmonary surfactant lipids in respiratory viral infections.